Exploring primary school teachers’ perceptions and approaches towards learning science teachers: A systematic literature review - Hardman, J.; Rzyankina, E. (South African Journal of Higher Education, 2026)
South African students perform extremely poorly on international benchmarking tests of science such as the Trends in Mathematics and Science Study (TIMSS). While there are several reasons for underperformance in science, ranging from lack of human and material resources to teachers’ lack of content knowledge in science, one the significant factors impacting science achievement in schools relates to how teachers teach the subject. We locate this article theoretically in the work of Vygotsky (1986) who conceives of learning as developmental and indicates how teaching can transform children cognitively. As the central mechanism for transmitting conceptual knowledge in a classroom, how teachers teach science and how they assume science should be taught is crucial to understanding students’ outcomes. In this systematic literature review, we investigate teachers’ perceptions of how science should be taught for optimal student outcomes as well as investigating what pedagogical methods lead to optimal learning.